DUTIES APPLIED TO THE PEDAGOGICAL ACTIVITY OF A PHYSICIAN-TEACHER (Scientific journal of the Fergana State University, 2024)
The article describes the modern requirements for pedagogic professional activity of medical students. It is said that one of the important tasks is to reform the education system based on science and achievements in the process of spiritual renewal.